OTOMATISASI PENDISTRIBUSIAN ZAKAT PADA BADAN AMIL ZAKAT NASIONAL PROV. KEP. BANGKA BELITUNG - Harrizki Arie Pradana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
Baznas Prov. Kep. Bangka Belitung is a zakat management body which was established based on law number 38 of 1999. Baznas is an agency that collects and distributes the zakat that is obtained. In the process of distributing zakat, there are things that are deemed ineffective, including overlapping data on residents who have received and who have never received it, as well as difficulties in making documents needed in the process of distributing zakat and infaq. Given these problems in the study it is proposed to build a computerized system. Object-oriented methods using the Unified Modeling Language as a tool used in the analysis and design. The technology used in system software development uses Phpp as the programming language and My SQL as the database. This system is expected to improve the performance of Baznas Prov. Kep. Bangka Belitung in terms of zakat distribution.